Carbon assimilation and accumulation of cyanophycin during the development of dormant cells (akinetes) in the cyanobacterium Aphanizomenon ovalisporum - Sukenik, Assaf; Maldener, Iris; Delhaye, Thomas; Viner-Mozzini, Yehudit; Sela, Dotan; Bormans, Myriam (Frontiers in Microbiology, 2015)
Akinetes are spore-like non-motile cells that differentiate from vegetative cells of filamentous cyanobacteria from the order Nostocales. They play a key role in the survival and distribution of these species and contribute to their perennial blooms. Here we demonstrate variations in cellular ultrastructure during akinete formation concomitant with accumulation of cyanophycin; a copolymer of aspartate and arginine that forms storage granules. Cyanophycin accumulation is initiated in vegetative cells few days post exposure to akinete inducing conditions. This early-accumulated cyanophycin pool in vegetative cells disappeared as a nearby cell differentiates to an akinete and stores large pool of cyanophycin. During the akinete maturation, the cyanophycin pool is further increased and comprise up to 2% of the akinete volume. The cellular pattern of photosynthetic activity during akinete formation was study by a nano-metric scale secondary ion mass spectrometry (NanoSIMS) analysis of 13C-enriched cultures. Quantitative estimation of carbon assimilation in vegetative cells and akinetes (filament-attached and free) indicates that vegetative cells maintained their basal activity while differentiating akinetes gradually reduced their activity. Mature free akinetes practically lost their photosynthetic activity although small fraction of free akinetes were still photosynthetically active. Additional 13C pulse chase experiments indicated rapid carbon turnover during akinete formation and de novo synthesis of cyanophycin in vegetative cells 4 days post induction of akinete differentiation.